Pelatihan Jaringan Digital Marketing Sebagai Sarana Penunjang Pemasaran Produk UMKM di Desa Sukopuro, Jabung, Kabupaten Malang Jawa Timur - Tri Kristianti; Wirawan Aryanto Balol; Peni Puspitasari (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2022)
Sukopuro Village has around a hundred MSME actors with processed local agricultural products which are dominated by cassava. The COVID-19 pandemic has reduced the number of orders for MSME products in Sukopuro Village. One of the factors causing delays in product marketing is the limited knowledge of MSME actors on how to sell boldly (online). This training aims to provide insight as well as the practice of creating a digital marketing network in order to increase the marketing of MSME products in Sukopuro Village, Jabung District, Malang Regency, East Java. This training is carried out in the following stages; 1) data collection by direct observation and observation, 2) preparation of counseling consisting of requests for permits to village officials, preparation of training materials and media used, 3) implementation of counseling by the process of providing material through offline media, 4) activity evaluation. The results of this counseling are aimed at helping participants who do not understand marketing strategies boldly (online) to understand how to have an email account and social media to be used as a means to market their MSME products.